Epidemiology of physical activity and sedentary behavior levels among patients entering treatment for substance use disorder in the United States: a descriptive study - Churchill, Sydney L.; Lansing, Jeni E.; Brellenthin, Angelique G.; Meyer, Jacob D. (Frontiers in Psychiatry, 2024)
Substance use disorder (SUD) is associated with poor mental and physical health. Little is known about physical activity behaviors among people with SUD. This study aimed to (1) describe self-reported moderate-to-vigorous physical activity (MVPA) and sedentary (SED) behaviors of adults with SUD initiating treatment, (2) determine the potential contributions of drug of choice (DOC) on these behaviors, and (3) determine the potential contributions of level of care and demographic variables on these behaviors. Secondary data that was collected via surveys including dDemographic information, psychological health, drug of choice, MVPA (categorized as inactive, insufficiently active, meets guidelines, exceeds guidelines) and SED (<4 h/day, 4-<6 h/day, 6-8 h/day, >8 h/day) were collected analyzed from 1,293 patients in inpatient/outpatient treatment facilities across the United States. On average, over half (51%) of patients entering treatment reported not meeting guidelines, but sitting time was generally low (median= 360 min/day). MVPA levels differed based on level of care (p<0.001) with 48% of patients in detox facilities reporting inactivity compared to 37% in residential and 29% in outpatient programs. MVPA and SED levels differed by sex with women less likely to report sitting <4 h/day (27.9% vs. 38.2%, p<0.001) and more likely to report sitting for >8 h/day (31.5% vs. 21.8%, p<0.001) compared to men. SED differed by race (p=0.01), with 54% of Black patients reporting <4 h/day compared to 33% of White patients. Understanding activity behaviors patterns among individuals entering SUD treatment provides opportunities for identifying the extent of lifestyle behavior needs and opportunities to develop personalized treatment strategies.